Opening up Military Innovation: Causal Effects of 'Bottom-up' Reforms to U.S. Defense Research - Sabrina T. Howell; Jason Rathje; John Van Reenen; Jun Wong (Institute of Labor Economics (IZA), 2021)
When investing in research and development (R&D), institutions must decide whether to take a top-down approach – soliciting a particular technology – or a bottom-up approach in which innovators suggest ideas. This paper examines a reform to the U.S. Air Force Small Business Innovation Research (SBIR) program that transitioned from "Conventional topics," which solicit specific technologies, to "Open topics," which invite firms to suggest any new technology that may be useful to the Air Force. The reform seeks to address challenges facing military R&D, in particular a less innovative defense industrial base. We show that the Open program attracts new entrants, defined as younger firms and those without previous defense SBIR awards. In a regression discontinuity design that offers the first causal evaluation of a defense R&D program, we show that winning an Open award increases future venture capital investment, non-SBIR defense contracting, and patenting. Conventional awards have no effect on these outcomes but do increase the chances of future defense SBIR contracts, fostering incumbency. The bottom-up approach appears to be a mechanism behind Open's success. For example, winning has a positive effect on innovation even in less specific Conventional topics. The results suggest that government (and perhaps private sector) innovation could benefit from more bottom-up, decentralized approaches that reduce barriers to entry, minimize lock-in advantages for incumbents, and attract a wider range of new entrants.
Keywords: O31; O32; O38; H56; H57; 330; innovation; defense; R&D; procurement